2007
DOI: 10.1017/s113874160000648x
|View full text |Cite
|
Sign up to set email alerts
|

Learned Changes in Stimulus Representations (A Personal History)

Abstract: Almost 40 years ago I began what turned out to be a programme of research on the way in which experience can change the effectiveness of the events used as stimuli in standard associative learning procedures. In this personal history I will describe my early (failed) attempts to find evidence for the acquired distinctiveness of cues, and my conclusion that experience tends to reduce, not enhance the associability of stimuli. I then go on to describe my attempts to square this conclusion with the stubborn empir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…For example, Honey and Hall (1989) reported that conditioned suppression generalized more readily from one CS to another if both stimuli had been previously associated with the same US (food pellets). Their findings indicate that generalization between two physically different stimuli can be increased if they are associated with a common event—in effect, by increasing the number of elements they share (e.g., Hall, 2007). Such acquired equivalence could contribute to secondary extinction because X and Y are associated with a common US during the initial conditioning phase.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Honey and Hall (1989) reported that conditioned suppression generalized more readily from one CS to another if both stimuli had been previously associated with the same US (food pellets). Their findings indicate that generalization between two physically different stimuli can be increased if they are associated with a common event—in effect, by increasing the number of elements they share (e.g., Hall, 2007). Such acquired equivalence could contribute to secondary extinction because X and Y are associated with a common US during the initial conditioning phase.…”
Section: Discussionmentioning
confidence: 99%